Ameliorative Effect of Urtica Dioica on the Hypothyroidism Induced By Propylthiouracil in Experimental Rats - Eman Hassan Abdel Aziz Sharaf (International Journal of Pharma and Bio Sciences, 2021)
This study aimed to evaluate the effect of Urtica dioica leaves aqueous extract (UD) on thyroid gland functions in propylthiouracil (PTU)-induced hypothyroidism in rats. Thirty male Wistar rats were randomly divided into 5 groups. Control group: daily received i.p injection of saline for 4 weeks. PTU group: (in drinking water to a final concentration of 500 mg/L) orally administered saline for 4 weeks. UD treated groups: orally administered 50, 100 or 150 mg/kg doses of UD for 4 weeks In blood samples, thyroid hormones (triiodothyronine (T3), free triiodothyronine (fT3), thyroxine (T4), and free thyroxine (fT4)), thyroid-stimulating hormone (TSH), antioxidant elements (Malondialdehyde (MDA), total antioxidant capacity (TAC), glutathione (GSH)), and lipid profile (triglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL-C) and low-density lipoprotein (LDL-C) was measured. The data showed that PTU decreased the blood level of thyroid hormones (T3, fT3, T4, and fT4), however increased TSH, significantly. The 100 or 150 mg/kg doses of UD remarkably increased the blood level of T3 and FT3. Also, serum levels MDA, total TAC, GSH, and lipid profile (TG, TC, HDL-C and LDL-C) was ameliorated. Thyroid tissues of hypothyroid rats showed flattening of the epithelial lining with several follicular cell degenerations, hyperplasia, cytoplasmic vacuolation and vascular congestion compared to the control group. Administration of UD ameliorated these changes with the 150 mg/kg being the most effective. The aqueous extract of UD could restore thyroid hormone profile, lipid profile and antioxidant factors in the hypothyroid rats in a dose-dependent manner.